2011
DOI: 10.1083/jcb.201008121
|View full text |Cite
|
Sign up to set email alerts
|

A single ubiquitin is sufficient for cargo protein entry into MVBs in the absence of ESCRT ubiquitination

Abstract: While ESCRT-0 is ubiquitinated by the Rsp5 E3 ligase, loss of Rsp5 does not disrupt monoubiquitin-dependent sorting into multivesicular bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
171
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(180 citation statements)
references
References 72 publications
7
171
2
Order By: Relevance
“…To this end, we expressed a dominantacting protein in which the ESCRT-0 subunit Hse1 (the homologue of mammalian STAM) is fused to the catalytic domain of the deubiquitinating peptidase domain of Herpes Virus UL36, resulting in the formation of an Hse1-DUb chimeric protein ( Fig 1A). Our previous studies showed that when Hse1-DUb is expressed in wild-type cells, either as the sole copy of Hse1 or in addition to endogenous Hse1, it effectively removes Ub from cargo during the MVB-sorting process, and blocks the sorting of a variety of cargoes that would normally undergo Ub-dependent sorting into MVB ILVs [7]. As a further measure of the effectiveness of Hse1-DUb to block MVB sorting of ubiquitinated cargo, we followed green fluorescent protein (GFP)-tagged Ub (GFP-Ub; [8]).…”
Section: Resultsmentioning
confidence: 99%
“…To this end, we expressed a dominantacting protein in which the ESCRT-0 subunit Hse1 (the homologue of mammalian STAM) is fused to the catalytic domain of the deubiquitinating peptidase domain of Herpes Virus UL36, resulting in the formation of an Hse1-DUb chimeric protein ( Fig 1A). Our previous studies showed that when Hse1-DUb is expressed in wild-type cells, either as the sole copy of Hse1 or in addition to endogenous Hse1, it effectively removes Ub from cargo during the MVB-sorting process, and blocks the sorting of a variety of cargoes that would normally undergo Ub-dependent sorting into MVB ILVs [7]. As a further measure of the effectiveness of Hse1-DUb to block MVB sorting of ubiquitinated cargo, we followed green fluorescent protein (GFP)-tagged Ub (GFP-Ub; [8]).…”
Section: Resultsmentioning
confidence: 99%
“…Ubiquitylation of PM proteins has been demonstrated in higher plants (6)(7)(8)(9)15), and, analogous to the situation in animals and fungi (30)(31)(32), covalent attachment of a single ubiquitin seems a sufficient signal for endocytosis and vacuolar targeting of selected PM proteins (7,8). This modification has been implicated in modulating abundance of nutrient carrier and light receptor proteins at the PM, thereby controlling intracellular solute homeostasis as well as stimulus-mediated growth responses (6)(7)(8).…”
Section: Resultsmentioning
confidence: 99%
“…Specificity for K63-linked chains, as opposed to multiple-mono-Ub, has been suggested by the cooperative binding K63 poly-Ub shows for the multiple UBDs within ESCRT-0 or a single UBD within yeast Vps36 (Kulathu et al 2009;Lange et al 2012b). However, these effects are moderate and a single Ub on cargo is sufficient to confer sorting into ILVs, indicating that the role of K63 chains may be to simply increase the number of mono-Ub sorting signals attached to cargo (Ren and Hurley 2010;Stringer and Piper 2011).…”
Section: Roles Of Multiple Ubdsmentioning
confidence: 99%
“…In experimental settings, namely, where Ub is permanently attached cargo, a single Ub is sufficient for delivery to lysosomes (Shih et al 2000;Raiborg et al 2002;Stringer and Piper 2011). However, as an internalization signal, a single Ub is exceptionally weak and Ub is likely operational only in chains (Barriere et al 2006;Hawryluk et al 2006;Bertelsen et al 2011).…”
Section: Ubiquitin-dependent Sorting In Endocytosismentioning
confidence: 99%